2022
DOI: 10.3390/antiox11091811
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Oxidative Stress in Intracerebral Hemorrhage: Prospects of the Natural Products Approach

Abstract: Intracerebral hemorrhage (ICH), the second most common subtype of stroke, remains a significant cause of morbidity and mortality worldwide. The pathological mechanism of ICH is very complex, and it has been demonstrated that oxidative stress (OS) plays an important role in the pathogenesis of ICH. Previous studies have shown that OS is a therapeutic target after ICH, and antioxidants have also achieved some benefits in the treatment of ICH. This review aimed to explore the promise of natural products therapy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 157 publications
0
3
0
Order By: Relevance
“…Pathophysiologically, a higher level of glucose fluctuation has been associated with the severity of systemic oxidative stress [35,36], which is considered as the key mechanism underlying the association between acute GV and cardiovascular complications in patients with diabetes. Interestingly, oxidative stress has been increasingly recognized as a key mechanism, which is responsible for the secondary brain injury in patients with ICH [37], probably via the induction the subsequent mechanisms involving inflammatory response, apoptosis, autophagy, and bloodbrain barrier disruption [38,39]. Therefore, it could be hypothesized that increased glucose fluctuation in patients with ICH may deteriorate the cerebral dysfunction by enhancing systemic oxidative stress inducing subsequent adverse molecular pathways, which may cause neural injury.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiologically, a higher level of glucose fluctuation has been associated with the severity of systemic oxidative stress [35,36], which is considered as the key mechanism underlying the association between acute GV and cardiovascular complications in patients with diabetes. Interestingly, oxidative stress has been increasingly recognized as a key mechanism, which is responsible for the secondary brain injury in patients with ICH [37], probably via the induction the subsequent mechanisms involving inflammatory response, apoptosis, autophagy, and bloodbrain barrier disruption [38,39]. Therefore, it could be hypothesized that increased glucose fluctuation in patients with ICH may deteriorate the cerebral dysfunction by enhancing systemic oxidative stress inducing subsequent adverse molecular pathways, which may cause neural injury.…”
Section: Discussionmentioning
confidence: 99%
“…Primary damage occurs within the initial hours after the onset of bleeding, primarily driven by the mass effect of the hematoma ( 15 ). Secondary damage refers to a cascade of reactions resulting from primary injury and the release of blood clot components, including excitotoxicity ( 16 , 17 ), oxidative stress ( 18 , 19 ), neuroinflammation ( 16 , 18 , 20 , 21 ), disruption of the blood–brain barrier (BBB) ( 21 , 22 ), ultimately leading to neuronal cell death ( 18 , 23 ). Of these, neuroinflammation mainly involves early activation of resident microglia, release of pro-inflammatory mediators and influx of peripheral immune cells ( 24 , 25 ).…”
Section: Overview Of Hemorrhagic Strokementioning
confidence: 99%
“…Oxidative stress has been implicated in the pathogenesis of a variety of common diseases, including stroke, hypertension, diabetes, neurodegenerative diseases, and malignancies [ 3 , 4 , 5 ]. In the study of a variety of diseases, many natural products have been found to be effective in regulating oxidative stress and thus exert anti-cancer properties [ 6 ] and the ability to treat intracerebral hemorrhage [ 7 ], diabetes, and neurodegenerative diseases due to an excessive inflammatory response [ 8 ]. This may be due to the unique free-radical-scavenging effect of plant-derived natural products [ 9 ].…”
Section: Introductionmentioning
confidence: 99%